The association between health literacy and screening for disease-specific complications among community-dwelling adults with diabetes - Nari, Fatima; Jun, Jae Kwan; Oh, Kyoung Hee; Jeong, Wonjeong (Frontiers in Public Health, 2024)
Introduction Diabetic retinopathy and nephropathy are examples of complications of uncontrolled diabetes. We hypothesized that health literacy has a defining role in understanding the importance of attending routine screening for diabetes complications. Therefore, our study investigated the relationship between verbal health literacy (VHL) and written health literacy (WHL) and screening for disease-specific complications in individuals with diabetes. Methods Cross-sectional data on 28,210 participants with diabetes was derived from the 2021 Korean Community Health Survey. Adjusted multiple logistic regression analysis was employed to investigate the association between VHL and WHL and diabetes complication screening. Further analysis was also carried out to further comprehend the relationship between those two forms of health literacy and other factors with diabetic retinopathy and nephropathy screening. Results Compared to those with high VHL, participants with low VHL had lower odds of diabetes complication screening; OR 0.89 (95% CI 0.84—0.95). The same was true for WHL, those who were uninterested reported the lowest odds ratio; OR 0.73 (95% CI 0.69—0.78), followed by low WHL; OR 0.88 (95% CI 0.82—0.94), of undergoing diabetes complication screening, when compared to individuals with high WHL. Our subgroup analysis presented similar results for diabetic nephropathy and retinopathy with both VHL and WHL. Conclusion Among individuals with diabetes, limited VHL and WHL was significantly associated with lower odds of diabetes complication screening. Interventions aimed at improving health literacy and associated health outcomes in the community setting are warranted.